2012
DOI: 10.1007/s12160-012-9346-9
|View full text |Cite
|
Sign up to set email alerts
|

AIDS-Related Stigma, HIV Testing, and Transmission Risk Among Patrons of Informal Drinking Places in Cape Town, South Africa

Abstract: Background AIDS-related stigma as a barrier to HIV testing has not been examined within the context of high at-risk environments such as drinking venues. Of particular importance is whether AIDS-related stigma is associated with HIV transmission risks among people who have never been tested for HIV. Purpose We examined: 1) AIDS-related stigma as a barrier to testing, controlling for other potential barriers, and 2) whether stigma is associated with HIV risks among HIV-untested individuals. Methods We surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 22 publications
(21 reference statements)
3
46
0
Order By: Relevance
“…29 Such an association was also suggested in different studies across the world. 15,17,21,22,30 The fear of losing jobs, verbal abuse, and family and social rejection was main reasons for nondisclosure in the study population, same as other studies. 8,31 According to Mbonu et al, 28 stigma and resultant depression could be a major cause for more risky behavior among the people.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…29 Such an association was also suggested in different studies across the world. 15,17,21,22,30 The fear of losing jobs, verbal abuse, and family and social rejection was main reasons for nondisclosure in the study population, same as other studies. 8,31 According to Mbonu et al, 28 stigma and resultant depression could be a major cause for more risky behavior among the people.…”
Section: Discussionsupporting
confidence: 71%
“…34 This adds to the existing debilitating state of these patients and pushes them to substance abuse. 15 The stigma associated with this was large even in the educational faculty. The assistant intern accompanying the research worker was discouraged by his colleagues stating that he may catch HIV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persons who did not provide consent for HIV testing were wealthier and more educated [8587]. HIV stigma is also a well known barrier to uptake of HIV testing in general [8890]. Furthermore, longitudinal data from the Malawi Diffusion and Ideational Change Project (MDICP) showed that persons who tested positive for HIV and received their results were less likely to consent to repeat testing in subsequent waves of the survey [91], and failure to adjust for selection bias has been shown to yield underestimates of national HIV prevalence [87,92].…”
Section: Discussionmentioning
confidence: 99%
“…In low- and middle-income countries (LMICs), HIV-related stigma has been associated with reduced uptake of voluntary counseling and testing[1,2] and increased sexual risk-taking behavior[3] in the general population. Among people living with HIV (PLHIV), stigma has been associated with emotional distress[4,5], decreased adherence to anti-retroviral therapy (ART)[6,7], and reduced likelihood of HIV status disclosure[8,9].…”
Section: Introductionmentioning
confidence: 99%